The correlation of wear with histological features after failed hip resurfacing arthroplasty - Grammatopoulos, G; Pandit, H; Glyn-Jones, S; Murray, D; Gill, H; Kamali, A; Maggiani, F; Athanasou, N (2013)
Background: Tissue necrosis and a macrophage and perivascular lymphocytic infiltrate are commonly seen in periprosthetic tissues around metal-on-metal hip resurfacing implants, including pseudotumors associated with these implants. The purpose of the present study was to correlate pathological changes in periprosthetic tissues with clinical findings and the amount of implant-derived metal wear. Methods: We analyzed morphological changes in the periprosthetic soft tissues around fifty-six failed metal-on-metal hip resurfacing implants. The most common reason for failure was the presence of a symptomatic pseudotumor (n = 45). The extent of necrosis and the nature of the inflammatory cell infiltrate, including aseptic lymphocyte-dominated vasculitis-associated lesion (ALVAL), was evaluated semiquantitatively. Bearing surface wear was determined for all patients. Prostheses were considered to be highly worn if the total linear wear rate was ≥4 μm/yr. Results: Substantial necrosis and a heavy macrophage infiltrate were noted in most periprosthetic tissues, including all pseudotumors, many of which contained a prominent ALVAL infiltrate. Most pseudotumors (80%) were associated with highly worn prostheses. It was noted that the extent of necrosis and macrophage infiltration correlated with the volume of generated metal wear. Although increased wear volume moderately correlated with a high ALVAL response, all pseudotumors associated with low wear had a strong ALVAL response. Conclusions: The majority of pseudotumors are associated with increased implant wear. This increased wear is associated with soft-tissue necrosis and a heavy nonspecific foreign-body macrophage response coupled with a variable adaptive or specific immune response (ALVAL). A minority of pseudotumors are associated with low wear and a prominent immune response. These findings confirm that minimizing wear from metal-on-metal hip resurfacing arthroplasty prostheses would lead to a reduction in the incidence of pseudotumor. However, a small number of pseudotumors are still likely to occur, which may be due to an exacerbated adaptive immune response. Level of Evidence: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence. Copyright © 2013 by The Journal of Bone and Joint Surgery, Incorporated.